An Analysis of Push and Pull Factors towards Purchase Intention to Shop at Batik Trusmi Cirebon - Zainal, Munawaroh; Wisastra, Agatha (ADI Publisher, 2021)
This research is design to analyze how the concept of push-and-pull factors positively impact the purchase intention at Batik Trusmi Cirebon. The research models are made to measure the impact between push factors and pull factors towards purchase intention. The research subject in this research is the customers who have shopped at Batik Trusmi Cirebon. 160 respondents are taken as samples and the data have been analyzed with multiple linear regression method. The result shows that push factors and pull factors are positively impact purchase intention. This means, both of the hypothesis are accepted. Batik Trusmi Cirebon could improve their marketing strategy such as promotion and quality consistency in order to attract more customers and other recommendation are made based on this research finding which is concluded in the last chapter.